Evaluación de tres tipos humedales artificiales (ornamental, forrajero, alimenticio) como depurador de aguas residuales grises en el bosque de la ESPAM - Mendoza Chavarría, Carlos Julio (2021)
The objective of this research was to evaluate three types of artificial wetlands (ornamental, forage and food) as purifiers of gray wastewater in the forest of the ESPAM “MFL”. In addition, the highest percentage of purification was determined with the purifying action of the plant species (Eichhornia crassipes, Chrysopogon zizanioides and Oryza sativa). To evaluate the wetland with the highest percentage of removal, a DCA was implemented consisting of three treatments that correspond to the three study plants (T1, T2 and T3 respectively) with four repetitions (R1, R2, R3 and R4) and a control, being effective study variables the species of plants used for purification or removal; The statistics projected as a result that the treatment with the highest percentage of removal was T2 or Chrysopogon zizanioides, with an average removal of 89,31%, with significant differences in two study parameters (BOD5, turbidity). According to T2, nitrogen obtained an average removal of 87,5%, phosphorous with 78,5%, BOD5 with 95,75% and turbidity with 95,5%. However, Dissolved Oxygen, pH and temperature for all the treatments acted as control factors since their removal percentage did not decrease; and regarding the treatment of rice or T3, the removal was good with 82,25%. These artificial wetlands are a technology that provides facilities in its implementation, with a low economic cost, valued at $ 90,37 and favors the care of the environment, so its promotion should be increased.